Adoption of ox-drawn minimum tillage ripping by smallholder farmers in Zambia. Issue 3 (3rd July 2021) - Sakala, Isabel C.; Kalinda, Thomson H.; Nkonde, Chewe; Burke, William J.
ABSTRACT: Applying a triple hurdle model to nationally representative farm household data from Zambia, this study examines determinants associated with three sequential crop production decisions: animal draught power adoption, minimum tillage ripping adoption, and the extent of hectares ripped. The correlated random effects estimator is also used to explore two dimensions of minimum tillage ripping adoption: changes in adoption within a household over time (within-household effect) and differences in adoption between households at a given time (between-household effect). Results reveal that age and gender of the household head, the head's level of education, household labour, hectares cultivated, ripper ownership, loan access, receiving conservation farming advice and distance to agricultural service providers are some of the key determinants associated with the three stages investigated using the triple hurdle model. The correlated random effects results demonstrate that while certain factors enhance or inhibit the expected value of hectares ripped within a given household, it is not always the case that these factors have a similar effect when the analysis is between households. This article highlights policy options to enhance ownership of rippers, support smallholder farmer access to loans, facilitate development of agro-dealer networks, and innovative approaches for disseminating conservation farming information to farmers.